Resources use, costs and effectiveness of non-penetrating deep sclerectomy according to glaucoma stage - Guedes,Ricardo Augusto Paletta (2011)
PURPOSE: To assess the resources use, costs and effectiveness of non-penetrating deep sclerectomy (NPDS). METHODS: A retrospective cohort of NPDS patients was analyzed. Eyes were stratified according to glaucoma severity into 3 groups: 1 (early), 2 (moderate) and 3 (severe). NPDS associated resources were based on the frequency of the following variables: surgical procedure (NPDS), intraoperative mitomycin C (MMC); 5-fluorouracil needling (5-FU); Nd:YAG laser goniopuncture; new filtering surgery and medications needed postoperatively. Costs were based on the value and prices of the Brazilian Public Health System and follow-up period was 5 years. Success rate: percentage of patients achieving an end-point intraocular pressure <18 mmHg (and least 20% reduction) without any medications. RESULTS: Percentage of patients using resources in groups 1, 2 and 3 was, respectively: 92.1%, 88.5% and 93.0% for MMC; 10.5%, 11.5% and 13.3% for 5-FU; 18.4%, 19.7% and 21.9% for goniopuncture and 13.2%, 24.6% and 27.3% for a new surgery. Mean number of glaucoma medications per patient at the end of follow-up was 0.42 in group 1 and 0.48 and 0.73 in groups 2 and 3, respectively. Mean NPDS direct cost was US$305.25, US$361.37 and US$390.09 in early, moderate and severe glaucoma, respectively. No differences were found in effectiveness according to glaucoma severity. CONCLUSION: There is a trend in the use of resources and costs in NPDS. The more advanced the glaucoma, the higher the need for resources and the higher the associated costs. NPDS effectiveness did not differ among different glaucoma stages.